The tending instinct how nurturing is essential for who we are and how we live - Taylor, Shelley E. 1946- (Times Books, 2002)
Taylor examines stress, relationships, and human society through the special lens of women's biology. She draws on genetics, evolutionary psychology, physiology, and neuroscience to show how this tending process begins virtually at the moment of conception and literally crafts the biology of offspring through genes that rely on caregiving for their expression. Taylor also examines what drives women to seek each other's company, and to tend to the young and the infirm -- acts that greatly benefit the group but often at great cost to the individual.